Pemanfaatan kekuatan media dalam pengelolaan event: studi kasus pengelolaan event borobudur marathon - Tarrence Karmelia Kontessa; Asep Sutresna (Jurnal Komunikasi Profesional, 2022)
Abstract The development of digital media has been a significant issue for media companies, particularly for those transformed from conventional media. Kompas daily, as one of the conventional media, should make some adjustments to this situation. As one of the responses to this issue, Kompas daily use event management as other source of revenue besides advertising. Borobudur Marathon is one of the events managed by this newspaper. It is an international event that started in 2017 and has been awaited by runners as well as Central Java people who host the event. This research uses qualitative approach, presenting data descriptively to reveal the strategy for the event management. The data were collected through in-depth interview to seven sources who had deep knowledge about Borobudur Marathon. The data were then analyzed and resulted in some findings. It was known that the media have the power to form opinion. This power was then beneficial for the event organizers to reach the goal of marketing communication, which later monetize this into one of the media revenue streams. Media Company and event organizers could use the finding of this research to reach the goals of effective and efficient marketing communication. Keywords: Event Management; Borobudur Marathon; Media Power; Opinion Formation; Marketing Communication